Study of Ruthenium Complex Sensitizer and Gold Nanoparticles Doped Flexible Organic Solar Cells. (29th September 2012) - Chen, Cheng-Chiang; Chen, Lung-Chien
Abstract : This work presents a flexible organic solar cell with a structure for ITO/PEDOT:PSS/P3HT:PCBM + r uthenium complex sensitizer and Au nanoparticles on a flexible substrate. The process and thickness of the PEDOT:PSS hole transport layer and P3HT:PCBM active layer were optimized. A ruthenium complex sensitizer and Au nanoparticles were then introduced into the P3HT:PCBM active layer to improve the performance of solar cells. For the ITO/PEDOT:PSS/P3HT:PCBM + r uthenium complex sensitizer and Au nanoparticles structure on a flexible polyimide (PI) substrate under 0.1 and 1 sun conditions, the measured short-circuit current density (J sc ), open-circuit voltage (V oc ), fill factor (FF), and efficiency ( η ) are 3.89 and 9.67 mA/cm 2, 0.45 and 0.45 V, 0.266 and 0.232, and 4.65 and 1.01%, respectively.